Influence of maternal diet during lactation and use of formula feeds on development of atopic eczema in high risk infants. Issue 6693 (22nd July 1989) - Chandra, R. K.; Puri, S.; Hamed, A.
Abstract : OBJECTIVE--To examine the effects of maternal diet during lactation and the use of formula feeds on the development of atopic eczema in infants at risk. DESIGN--Mothers who planned to breast feed exclusively were randomly allocated to either a restricted diet (avoiding milk and other dairy products, eggs, fish, peanuts, and soybeans) or a diet without restrictions. Mothers who did not plan to breast feed were randomly allocated to using one of three formula feeds. SETTING--Child health centre in Canada. SUBJECTS--97 Mothers who chose to breast feed and 124 mothers who did not. INTERVENTIONS--Restricted diet for 49 mothers who breast fed. Casein hydrolysate formula, soy milk formula, or cows' milk formula for infants not breast fed. MAIN OUTCOME MEASURE--Development of eczema in babies. RESULTS--Infants were followed up over 18 months and examined for eczema. Eczema was less common and milder in babies who were breast fed and whose mothers were on a restricted diet (11/49 (22%) v 21/48 (48%)). In infants fed casein hydrolysate, soy milk, or cows' milk 9/43 (21%), 26/41 (63%), and 28/40 (70%), respectively, developed atopic eczema. CONCLUSIONS--In families with a history of atopic disease [corrected] mothers who breast feed should avoid common allergenic foods during lactation. If they choose not to breast feed a hydrolysate formula should be used.